Teachers’ Perspectives on the Use of Physical Games in English Language Teaching - Fajrinur Fajrinur; Zurina Zora (Jurnal Ilmiah Guru Madrasah, 2025)
This study explores teachers’ perspectives on the use of physical games in English language teaching within school-based EFL contexts. Employing a descriptive qualitative design, data were collected through semi-structured interviews with eight secondary school English teachers who had experience using physical games in their classrooms. The data were analyzed using thematic analysis to identify recurring patterns in teachers’ perceptions and experiences. The findings reveal that teachers generally perceive physical games as a beneficial instructional approach, particularly for supporting vocabulary learning, speaking practice, and students’ motivation and engagement. Teachers reported that physical games encouraged active participation and reduced students’ anxiety in using English. However, the study also identifies several challenges in implementing physical games, including classroom management difficulties, limited instructional time, large class sizes, and restricted physical space. To address these challenges, teachers employed various adaptive strategies, such as selecting simpler games, establishing clear classroom rules, and modifying activities to fit contextual constraints. The study highlights that teachers’ perspectives on physical games are both positive and pragmatic. The findings suggest that physical games can be effectively integrated into English language teaching when they are carefully planned, contextually adapted, and aligned with instructional objectives. This study contributes to the understanding of physical games from the perspective of teacher cognition and offers practical insights for sustainable implementation in EFL classrooms.